A new annual fish of the genus Austrolebias (Cyprinodontiformes: Rivulidae) from Rio Camaquã basin, Laguna dos Patos system, Brazilian Pampa - Volcan, Matheus Vieira; Gonçalves, Ândrio Cardozo; Lanés, Luis Esteban Krause (Zootaxa, 2017)
A new species of Austrolebias is described from the middle course of the Rio Camaquã, Laguna dos Patos system, Rio Grande do Sul, Brazil. The new species belongs to the Austrolebias alexandri species group, which is distinguished from the remaining congeners by the presence of a dark gray pectoral fin with bright blue iridescence in males. The new species is distinguished from all remaining species of the A. alexandri species group by the following combination of characters: presence of well-defined bright blue bars on the flank in males, shorter caudal fin length in males and females, contact organs in the first three rays of the pectoral fin in males, one to two post-optic neuromasts (rarely three), basihyal width of 50% of the length, and basihyal cartilage about 50–60% of the basihyal length. The recognition of this new species belonging to the A. alexandri group endemic of the middle course of Rio Camaquã and the recent discovery of Austrolebias bagual in the same general region reinforces the claim of the middle Rio Camaquã basin as an area of endemism for annual fishes and as such, a priority area for conservation in southern Brazil.